Comparison of the analytical performance of the Oncomine dx target test focusing on bronchoscopic biopsy forceps size in non‐small cell lung cancer. Issue 10 (5th April 2022) - Sakaguchi, Tadashi; Nishii, Yoichi; Iketani, Akemi; Esumi, Seiya; Esumi, Maki; Furuhashi, Kazuki; Nakamura, Yuki; Suzuki, Yuta; Ito, Kentaro; Fujiwara, Kentaro; Katsuta, Koji; Taguchi, Osamu; et al.
Abstract: Background: Next‐generation sequencing (NGS) has been implemented in clinical oncology to analyze multiple genes and to guide targeted therapy. Although the pathological diagnosis and biomarker tests for patients with advanced lung cancer have mostly been obtained with small biopsy samples, especially with bronchoscopic approaches, the performance for NGS with respect to the different sizes of biopsy forceps remains little known. Methods: We retrospectively reviewed consecutive patients with non‐small cell lung cancer, whose FFPE samples were obtained by endobronchial biopsy/transbronchial biopsy and were submitted for the Oncomine Dx Target Test (ODxTT). We compared the analytical performance for ODxTT with respect to the size of biopsy forceps. Results: A total of 103 samples were identified. The success rate of the ODxTT for the group with all samples obtained with small forceps biopsies (70%) was lower than that of the group with some or all samples obtained with standard forceps biopsies (83%), although without a statistically significant difference ( p  = 0.20). With regard to the reason for unsuccessful analysis, the proportion of the samples which did not pass the nucleic acid concentration threshold in the former group (15%) was higher compared with that of the latter group (4%) ( p  = 0.08). The proportion of tissue size 4 mm 2 or larger in the former group (70%) was lower than that in the latter group (93%) ( p  = 0.01). Conclusion: The analysis of ODxTT for specimens biopsied using only small forceps is prone to be unsuccessful due to an insufficient amount of nucleic acid. Abstract : Among a total of 103 samples obtained by endobronchial biopsy/transbronchial biopsy, the success rate of the ODxTT for the group with all samples obtained with small forceps biopsies (70%) was lower than that of the group with some or all samples obtained with standard forceps biopsies (83%). As for the reason for unsuccessful analysis, the proportion of the samples which did not pass the nucleic acid concentration threshold in the former group (15%) was higher compared with that of the latter group (4%).